Confrontational Argumentative Strategies in the Discourse of Foreign Policy Experts - Allani, Samira (Research in Language, 2019)
The aim of this study is to explore the discursive practices of foreign policy experts. While policy decisions involving war and peace keep people alarmed all over the globe, most of these decisions are shaped by policy experts who work on influencing public opinion through the media (Manheim, 2011). This study adopts a critical discursive stance and uses argumentation analysis to examine the ideological backdrop to the discourse of thirty opinion articles authored by American foreign policy experts in print media. Drawing on the Pragma-dialectical method of augmentation analysis (van Eemeren and Grootendorst, 2004), and more particularly on its notion of strategic maneuvering, the analysis examines the confrontational strategies used by this group of experts and attempts to determine the rhetorical goals pursued by these strategic maneuvers.